Recent Commercial Free-Piston Engine Developments for Automotive Applications - Mohd Razali, Hanipah; R., Mikalsen; A. P., Roskilly (Elsevier Ltd, 2015)
Free-piston engines have been under extensive investigation in recent years, however have not yet seen commercial success in modern applications. This paper reviews some of the recently reported commercial developments in free-piston engine systems particularly aimed for use in hybrid electric vehicle powertrains and discuss these in light of published research. By looking at recent publications, and in particular patent documents, from major industrial players, insight into the less widely reported commercial research efforts on free-piston engines is obtained. Further, these publications provide a useful indication as to what these developers see as the main technical challenges for this technology.